Welfare Effects of Policy-induced Rising Food Prices on Farm Households in Nigeria (2014)
Against the background that domestic policies in Nigeria have been linked to an endemic - high, volatile and rising food prices in the country, this paper empirically examined the transmission of key monetary policy variables to domestic food prices in Nigeria. Furthermore, the study employed estimates of policy induced price changes from estimated cointegrating relations between commodity prices and policy variables, and demand elasticities from a system of household demand equations to estimate the associated compensating variation as a measure of the welfare impacts on farm households. The study found that government management of exchange rates and money supplies as well as withdrawal of subsidies from petroleum products have been the main driver of rising food prices in the country. While an average farmer was found to have benefited from the policy induced rising food prices with the mean compensated variation of -3.3% of the household budget, most of the farm households ended up being losers. The gainers were mostly owners of the relatively few large farms (-36.9%) including the commercial livestock farms (-38.9%), rice farm (-35.0%), and fish farms (-27.8%). Smallholders, which constituted about three-quarter of the farm households, lost on the average, about 8.1% of their purchasing power to the rising food prices, with female headed households also loosing 6.6% of their purchasing power.